2002
DOI: 10.14710/jksa.5.1.12-14
|View full text |Cite
|
Sign up to set email alerts
|

Optimasi Waktu Destilasi Uap dan Identifikasi Komponen Minyak Kulit Jeruk Siam (Citrus Nobilis L.)

Abstract: ABSTRAK Aroma jeruk banyak digunakan dalam berbagai produk makanan, minuman, kosmetika dan farmasi. Aroma jeruk alami berasal dari minyak atsiri, mudah diperoleh dari kulit buah jeruk. Salah satu jeruk yang banyak dimanfaatkan sebagai minuman adalah jerukSiam. Sisa pembuatan minuman jeruk dapat dimanfaatkan sebagaipenghasil minyak atsiri. Isolasi minyak atsiri dari kulitjeruk siam (Citrus nobilis L) telah dilakukan dengan metode distilasi uap. Waktu distilasidivariasi untuk menentukan waktu optimum. Selanjutny… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Thus, the faster the material reaches its boiling point for the evaporation process (Hien et al, 2022). Several research results related to extraction time were reported by Haryanti et al, (2014), reporting the process of extracting orange fern oil in 3 h; Ikarini et al, (2021) reported that the distillation of Siamese oranges was carried out for 2 h; Febrina & Sigiro (2021) reported that the distillation of Siam Sambas oranges was carried out for 7 h; Fachriyah et al, (2002), reported distillation of Siamese orange peel essential oil for 10 h; Wibaldus et al, (2016) reported the distillation of lime for 4 h. The distillation time varies greatly also depending on the raw material, the thicker the orange peel, the longer the distillation time is needed. General, the Semboro Siamese orange peel with an average thickness of 1 mm.…”
Section: Distillation Process Temperaturementioning
confidence: 99%
“…Thus, the faster the material reaches its boiling point for the evaporation process (Hien et al, 2022). Several research results related to extraction time were reported by Haryanti et al, (2014), reporting the process of extracting orange fern oil in 3 h; Ikarini et al, (2021) reported that the distillation of Siamese oranges was carried out for 2 h; Febrina & Sigiro (2021) reported that the distillation of Siam Sambas oranges was carried out for 7 h; Fachriyah et al, (2002), reported distillation of Siamese orange peel essential oil for 10 h; Wibaldus et al, (2016) reported the distillation of lime for 4 h. The distillation time varies greatly also depending on the raw material, the thicker the orange peel, the longer the distillation time is needed. General, the Semboro Siamese orange peel with an average thickness of 1 mm.…”
Section: Distillation Process Temperaturementioning
confidence: 99%